ОСОБЕННОСТИ МАРКЕТИНГОВЫХ КОММУНИКАЦИЙ ВЫСШИХ УЧЕБНЫХ ЗАВЕДЕНИЙ МОЛДОВЫ - Райлян, Елена (CEP USM, 2024)
The article reflects the results of a desk study of the features of marketing communications of six higher education institutions of the country with the purpose of optimizing the communication policy of universities. The analysis of promotion techniques allowed us to identify all the promotion tools used by universities: advertising, PR, sales promotion, personal sales and direct marketing. The most used promotion techniques among universities were determined to be PR and direct marketing. Traditional advertising is little used by universities. The analysis of university websites determined the completeness of the use of all communication channels and recommendations were proposed for optimizing the promotion mix to build a positive image of universities and attract the target audience.
FEATURES OF MARKETING COMMUNICATIONS OF HIGHER EDUCATIONAL INSTITUTIONS IN MOLDOVA
РАЙЛЯН, Елена. Особенности маркетинговых коммуникаций высших учебных заведений Молдовы. In: Integrare prin cercetare și inovare: conferință științifică națională cu participare internațională. Științe Sociale, Chișinău, 7-8 noiembrie, 2024. Chișinău: CEP USM, 2024, pp.171-178. ISBN 978-9975-62-687-3; ISBN 978-9975-62-799-3 (PDF).
Keywords: advertising; direct marketing; marketing communications; promotion mix; universities